Effect of Betahistine and Metformin on Antipsychotic-Induced Weight Gain: An Analysis of Two Clinical Trials - Kang, Dongyu; Jing, Zhihui; Li, Ranran; Hei, Gangrui; Shao, Tiannan; Li, Li; Sun, Mengxi; Yang, Ye; Wang, Ying; Wang, Xiaoyi; Long, Yujun; Huang, Xiansheng; et al. (Frontiers in Psychiatry, 2018)
Antipsychotic-induced weight gain is one of the most common adverse effects of antipsychotic treatment. However, there are no well-established interventions for the weight gain yet. In this study, we pooled the data from two clinical trials, which were originally examining the efficacy of betahistine and the efficacy of metformin in treating antipsychotic-induced weight gain and insulin resistance. A total of 67 people with schizophrenia or bipolar disorder treated with antipsychotics were assigned to 36 mg day−1 betahistine (n = 13) or 1,000 mg day−1 metformin (n = 25) or placebo (n = 29) treatment for 12 weeks, with evaluation at baseline and week 12. The primary outcome was the body mass index (BMI). After treatment, metformin group had a mean decrease in BMI of 1.46 ± 0.14 (p < 0.001) and insulin resistance index (IRI) of 4.30 ± 2.02 (p < 0.001). The betahistine group had no significant alteration in BMI or IRI. However, placebo group had a mean increase in BMI of 1.27 ± 0.77 (p < 0.001) and IRI of 0.45 ± 0.86 (p < 0.001). Between the two treatment groups, metformin significantly decreased weight, BMI, fasting glucose, insulin level, and IRI but not waist circumference when compared with betahistine. Moreover, metformin significantly decreased weight, BMI, waist circumference, fasting glucose, insulin level, and IRI when compared with placebo, whereas betahistine significantly decreased body weight, waist circumference, BMI, insulin level, and IRI but not fasting glucose when compared with placebo. In this study, we found that both metformin treatment and betahistine treatment were efficacious in improving antipsychotic-induced weight gain and insulin resistance, and metformin was more efficacious in preventing and revising the weight gain induced by antipsychotics. Clinical Trial Registration:www.ClinicalTrials.gov, NCT00451399(Study 1), NCT00709202(Study 2)